2021
DOI: 10.3390/app11104375
|View full text |Cite
|
Sign up to set email alerts
|

Characterising Modal Behaviour of a Cantilever Beam at Different Heating Rates for Isothermal Conditions

Abstract: The effect of temperature on structural response is a concern in engineering applications. The literature has highlighted that applied temperature loads change the system vibration behaviour. However, there is limited information available about temperature impacting the dynamic response. This paper investigated the heating rates effects on modal parameters for both with crack and without crack conditions in a cantilever beam. A beam subjected to three heating rates was considered: 2, 5, and 8 °C/min. The firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
(50 reference statements)
0
7
0
Order By: Relevance
“…The modal behavior of the beam was examined at three heating rates, as discussed in a previous paper [40]. The modal characteristic of the beam in uniform temperature was presented in a previous paper [40]. This paper analyzed the beam response under non-uniform temperature conditions and comparison of the modal dynamics in both temperatures.…”
Section: Modal Behavior Of a Beam Under Uniform And Non-uniform Temperaturementioning
confidence: 99%
See 2 more Smart Citations
“…The modal behavior of the beam was examined at three heating rates, as discussed in a previous paper [40]. The modal characteristic of the beam in uniform temperature was presented in a previous paper [40]. This paper analyzed the beam response under non-uniform temperature conditions and comparison of the modal dynamics in both temperatures.…”
Section: Modal Behavior Of a Beam Under Uniform And Non-uniform Temperaturementioning
confidence: 99%
“…Solving the free vibration equation of the beam as discussed in our previous paper [40], we obtained the fundamental frequency of the beam expressed as:…”
Section: Analytical Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Hernandez et al presented a kinematic study of origami structures for both elastic and plastic polymeric beams. After assessing various design structures, it was found that the kinematic variables of the structural model could fully explain the configuration of elastic origami structures within the beam [ 21 , 22 ]. However, the model developed by the researcher is far more complete and needs fewer variables for efficient FEA.…”
Section: Introductionmentioning
confidence: 99%
“…These structures can experience fatigue failure due to dynamic loads in a complex thermo-mechanical environment [10][11][12]. Compared with other materials [13][14][15][16][17], the crack propagation during fatigue is highly complicated for FDM polymeric structures because of the significant differences in its microstructure due to various printing parameters.…”
Section: Introductionmentioning
confidence: 99%